Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1074/jbc.m409130200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of All-trans-Retinol:All-trans-13,14-dihydroretinol Saturase

Abstract: Retinoids carry out essential functions in vertebrate development and vision. Many of the retinoid processing enzymes remain to be identified at the molecular level. To expand the knowledge of retinoid biochemistry in vertebrates, we studied the enzymes involved in plant metabolism of carotenoids, a related group of compounds. We identified a family of vertebrate enzymes that share significant similarity and a putative phytoene desaturase domain with a recently described plant carotenoid isomerase (CRTISO), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 62 publications
5
117
0
1
Order By: Relevance
“…RetSat has been shown to catalyze the conversion of retinol to 13,14-dhretinol (16), and thus we hypothesized that this retinoid would rescue the effect of RetSat ablation during differentiation. Surprisingly, however, 13,14-dhretinol did not compensate for the effect of RetSat ablation (Fig.…”
Section: Retsat Is Required For Normal Adipocyte Differentiation Downmentioning
confidence: 99%
See 1 more Smart Citation
“…RetSat has been shown to catalyze the conversion of retinol to 13,14-dhretinol (16), and thus we hypothesized that this retinoid would rescue the effect of RetSat ablation during differentiation. Surprisingly, however, 13,14-dhretinol did not compensate for the effect of RetSat ablation (Fig.…”
Section: Retsat Is Required For Normal Adipocyte Differentiation Downmentioning
confidence: 99%
“…In the search for missing pieces of adipose retinoid metabolism, we found that the oxidoreductase retinol saturase (RetSat), which has been described to catalyze the reaction of retinol to 13,14-dihydroretinol (dhretinol) (16), is induced during murine and human fat cell differentiation. RetSat expression is controlled by PPAR␥ through an intronic PPAR␥ response element (PPRE) in adipocytes.…”
mentioning
confidence: 99%
“…In addition to these cellular events, adipose tissue and renal physiology may also be altered as suggested by the response of a retinol saturase enzyme (RetSat, all-trans-retinol reductase) that has a > 2-fold increase in expression and by the > 2-fold repression of a Na + /H + exchange regulatory factor (NHE-RF1). RetSat is probably involved in vitamin A (or retinol) metabolism and adipose tissue physiology through adipocyte differentiation (Moise et al 2004(Moise et al , 2010. The lack of knowledge about this role precludes any further interpretation regarding a potential alteration of retinoid metabolism or adipose tissue physiology.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions were carried out at 30°C for 2 min and then quenched by the addition of 100 l of methanol. Retinoids were extracted with 200 l of hexane and analyzed on a HewlettPackard 1100 series HPLC system equipped with a diode array detector and a Beckman Ultrasphere Si normal-phase column (5 m, 4.5 ϫ 250 mm) (32). The initial velocity data were analyzed using the Michaelis-Menten equation by nonlinear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We transiently transfected COS-7 cells to study the targeting and distribution of WT LRAT and its truncation mutants. Formation of retinosomes (retinyl ester storage particles) was studied in vitro in stably transfected HEKK-LRAT cells, which express mouse WT LRAT under the control of a tetracycline-inducible promoter (32). Cells were cultured in complete Dulbecco's modified Eagle's medium on glass-bottom microwell dishes (MatTek Corp., Ashland, MA).…”
Section: Methodsmentioning
confidence: 99%